Human trafficking and four false truths (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The paper addresses issues regarding human trafficking that are conceived as undeniable truths. First, it focuses on the linguistic approach of the expression human trafficking. The high number of victims, the feeling that nothing has changed in the last decades, the underground aspect of the crime and the view of human trafficking as isolated crime represent the four main points of attention. In the end, it is concluded that the awareness and the involvement of civil society are indispensable elements to confronting the problem.
Keywords: human trafficking; victims; forced labor; globalization; corruption